E-cigarettes in ten Southeast Asian countries: a comparison of national regulations - Pingyue Jin; Johnny Yu Jiang (Global Health Journal, 2017)
The market and popularity of e-cigarettes are growing rapidly worldwide. However, the research and regulation of this novel products have lagged behind. In this paper, we reviewed and compared the regulatory mechanisms regarding e-cigarettes among ten Association of Southeast Asian Nations (ASEAN) member states. Our findings demonstrated a continuum of the legal regulations of e-cigarettes in this region: on the one hand, countries such as Brunei, Cambodia, Thailand, and Singapore have prohibited the importation and sale of e-cigarettes with existing tobacco control laws or specific regulations; on the other, countries such as Myanmar and Vietnam had almost no legal restrictions on e-cigarettes whatsoever. This overview of national regulations not only clarified the legal status of e-cigarettes in the ASEAN region but also provided informing lessons for countries currently lacking e-cigarette regulations such as China.